Liver Fibrosis Scores and Clinical Outcomes in Patients With COVID-19 - Zhang, Jing; Liu, Fuwei; Song, Tiangang; Li, Zhangwang; Xia, Panpan; Tang, Xiaoyi; Xu, Minxuan; Shen, Yunfeng; Ma, Jianyong; Liu, Xiao; Yu, Peng (Frontiers in Medicine, 2022)
Background & Aims: We aim to assess the unknown association between liver fibrosis scores and clinical outcomes in patients with COVID-19. Methods: We conducted a post-hoc analysis from the ORCHID study (Patients with COVID-19 from the Outcomes Related to COVID-19 Treated with Hydroxychloroquine among Inpatients with Symptomatic Disease). The relationship between AST to platelet ratio index [APRI], Non-alcoholic fatty liver disease fibrosis score [NFS], Fibrosis‐4 index [FIB‐4], and discharge and death through 28-days were explored. Results: During 28 days after randomization, 237 (80.6%) patients were discharged and 31 (10.5%) died among 294 patients with COVID-19. Prevalence for advanced fibrosis was estimated by 34.0%, 21.8, 37.8% for FIB-4 (>2.67), APRI (>1.0), and NFS (>0.676), respectively. In multivariate analysis, FIB-4>2.67 (28-days discharge: hazard ratio [HR],0.62; 95% confidence interval [CI], 0.46–0.84; 28-days mortality: HR, 5.13; 95%CI, 2.18–12.07), APRI >1.0 (28-days discharge: HR,0.62; 95% CI, 0.44–0.87; 28-days mortality: HR, 2.85, 95%CI, 1.35–6.03) and NFS>0.676 (28-days discharge: HR,0.50; 95%CI, 0.35–0.69; 28-days mortality: HR, 4.17; 95%CI, 1.62–10.72) decreased significantly discharge rate and increased the risk of death. Additional, FIB-4, APRI, and NFS have a good predictive ability and calibration performance for 28-days death (C-statics: 0.740 for FIB-4, 0.657 for APRI and 0.745 for NFS) and discharge (C-statistic: 0.649 for FIB-4, 0.605 for APRI, 0.685 for NFS). Conclusion: In hospitalized patients with COVID-19, FIB-4, APRI, and NFS may be a good predictor for death and discharge within 28 days. The link between liver fibrosis and the natural history of COVID-19 should be further evaluated.